YY1 binding is a gene-intrinsic barrier to Xist-mediated gene silencing - Bowness, JS; Almeida, M; Nesterova, T; Brockdorff, N (EMBO Press, 2024)
X chromosome inactivation (XCI) in mammals is mediated by Xist RNA which functions in cis to silence genes on a single X chromosome in XX female cells, thereby equalising levels of X-linked gene expression relative to XY males. XCI progresses over a period of several days, with some X-linked genes silencing faster than others. The chromosomal location of a gene is an important determinant of silencing rate, but uncharacterised gene-intrinsic features also mediate resistance or susceptibility to silencing. In this study, we examine mouse embryonic stem cell lines with an inducible Xist allele (iXist-ChrX mESCs) and integrate allele-specific data of gene silencing and decreasing inactive X (Xi) chromatin accessibility over time courses of Xist induction with cellular differentiation. Our analysis reveals that motifs bound by the transcription factor YY1 are associated with persistently accessible regulatory elements, including many promoters and enhancers of slow-silencing genes. We further show that YY1 is evicted relatively slowly from target sites on Xi, and that silencing of X-linked genes is increased upon YY1 degradation. Together our results suggest that YY1 acts as a barrier to Xist-mediated silencing until the late stages of the XCI process.